Dual Band Rectifying Circuit For Rf Energy Scavenging - Meor Said, Maizatul Alice; Zakaria, Zahriladha; Husain, Mohd Nor; Abu, Maisarah; Mohd Salleh, Noor Hasyierah; Misran, Mohamad Harris (Asian Research Publishing Network (ARPN), 2016)
This paper reports the design and experimental characterization of a dual-band rectifier for RF energy scavenging. The proposed circuit achieves comparable performances at 1.8 GHz and 2.45 GHz (GSM and ISM bands) for the wireless sensor network (WSN) system. The efficiency of RF-DC conversion can be improve by influence of the rectifying circuit. The analysis is conducted using ADS simulation version 2011, to determine the dc output voltage as well as the efficiency of the rectifier. The results show the rectifier efficiencies around 74.6% at 2.45 GHz and 78.06% at 1.8 GHz. DC output voltages is 6.7 V for simulation, while for measurement the output result is 5.2 V at input signal 20 dBm. The resulting rectifier has shown good effect of input power, load changes and matching circuit with single stub impedance matching, multi stage Wilkinson power combiner and voltage doubler to implement the dual band operation. This study is useful to provide understanding on the optimum technique to design dual-band rectifying circuit for RF energy scavenging. RF signal is used to powered the rectifier including the two frequencies of interest.